Lactate dynamics in elite weightlifters during eight weeks of training - Sivokhin, I. P.; Skotnikov, V. F.; Tapsir, M.; Komarov, O. Y.; Utegenova, B. M.; Fedorov, A. I. (Theory and Practice of Physical Culture, 2017)
Objective of the study was to analyze the lactate concentration dynamics in elite weightlifters during an eight-week training cycle. Conclusion: The study showed that biochemical control of the lactate dynamics is a sensitive indicator of the athletes` bodies` reaction to the training load and can be used to control the training process in weightlifting. The study provided new information about the processes that occur in the athletes' bodies impacted by the training load of speed and strength type. Such data provide an opportunity to assess various components of the training load and ensure further improvement of various models of the training process.